Edukasi Terapi Spiritual: Dzikir Dalam Menurunkan Kekambuhan Halusinasi Pendengaran di Wilayah Kerja Puskesmas Bontomate’ne - Suid, Nurafni (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this community service is to provide socialization of Dzikir therapy at Puskesmas Bontomate’ne, which will serve as the foundation for designing more targeted and needs-based interventions. This community service consists of five stages. First, identifying participants and preparing the Dzikir therapy module. Second, collecting baseline data to assess the level of relapse in patients before the intervention. Third, implementing regular Dzikir therapy with supervision from the service team. Fourth, gathering follow-up data to evaluate changes after therapy. Lastly, analyzing and evaluating the results, which are then socialized to the relevant parties. This process is carried out with a participatory approach, involving patients, their families, and professional staff. Based on the results of the community service, it can be concluded that Dzikir therapy has a positive impact on reducing relapse levels in patients with auditory hallucinations. Before the Dzikir therapy, the majority of patients showed severe relapse levels, with 10 patients (55.6%). However, after the therapy, most patients experienced a reduction in relapse severity, reflected in 11 patients (61.1%) showing improvement. This indicates that Dzikir therapy can be an effective alternative intervention to help patients experiencing auditory hallucinations, especially those in outpatient care at Puskesmas Bontomate’ne, in reducing symptoms and supporting the recovery process.